The role of visual feedback on power output during intermittent Wingate testing in ice hockey players - Stastny, P.; Tufano, J. J.; Kregl, J.; Petr, M.; Blazek, D.; Steffl, M.; Roczniok, R.; Fiala, M.; Golas, A.; Zmijewski, P. (Sports, 2018)
Background: Visual feedback may help elicit peak performance during different types of strength and power testing, but its effect during the anaerobic Wingate test is unexplored. Therefore, the purpose of this study was to determine the effect of visual feedback on power output during a hockey-specific intermittent Wingate test (AnWT6x6) consisting of 6 stages of 6 s intervals with a 1:1 work-to-rest ratio. Methods: Thirty elite college-aged hockey players performed the AnWT6x6 with either constant (n = 15) visual feedback during all 6 stages (CVF) or restricted (n = 15) visual feedback (RVF) where feedback was shown only during the 2nd through 5th stages. Results: In the first stage, there were moderate-to-large effect sizes for absolute peak power (PP) output and PP relative to body mass and PP relative to fat-free mass. However, the remaining stages (2-6) displayed small or negligible effects. Conclusions: These data indicate that visual feedback may play a role in optimizing power output in a non-fatigued state (1st stage), but likely does not play a role in the presence of extreme neuromuscular fatigue (6th stage) during Wingate testing. To achieve the highest peak power, coaches and researchers could provide visual feedback during Wingate testing, as it may positively influence performance in the early stages of testing, but does not result in residual fatigue or negatively affect performance during subsequent stages